Evaluation of electrochemical performance of antimony modified screen-printed carbon electrodes - Alexander B. Kifle; Nataliya Malakhova; Alexandra Ivoilova; Natalia Leonova; Svetlana Saraeva; Alisa Kozitsina (Chimica Techno Acta)
This study compares the electrochemical performance of screen-printed carbon electrodes (SPCEs) modified with antimony (Sb/SPCEs) under different potentiostatic pre-plating conditions. Neutral Red (NR) was employed as a novel redox probe to evaluate the electrochemical performance of Sb/SPCEs. It was demonstrated that NR in the protonated form performs quasi-reversible redox transformations at bare SPCE and Sb/SPCEs in phosphate buffer solutions (pH 5.5±0.5) in the potential range of (−0.30)–(−0.75) V, where the antimony is not electroactive. Sb/SPCEs were studied electrochemically by cyclic voltammetry (CV) / electrochemical impedance spectroscopy (EIS), and morphologically by scanning electron microscopy (SEM). Cyclic voltammetry investigations revealed the dependence of the electrochemical performance of Sb/SPCEs on the degree of coverage of the substrate with the metal. The obtained CV, EIS, and SEM data are consistent. The lowest charge transfer resistance (Rct) value (6 Ω) was obtained at Sb/SPCE with the highest degree of antimony coverage. To investigate the electroanalytical performance of Sb/SPCEs, nickel (II) ions were utilized as a model analyte. A study of roughness factors and sensitivity towards nickel (II) ions for Sb/SPCEs using two-tailed Pearson's criterion revealed a high degree of correlation between their electrochemical and electroanalytical properties. The results show that using NR as a redox probe can help controlling modification processes during the development of innovative antimony-containing sensors.